2021
DOI: 10.1111/ntwe.12215
|View full text |Cite
|
Sign up to set email alerts
|

The impact of artificial intelligence on skills at work in Denmark

Abstract: Based on a unique dataset on the use of artificial intelligence (AI) among employees in Denmark, we investigate within-job relationships between AI use and skill requirements. We show that the effects of AI are varied and depend on whether AI is used for providing orders to humans or providing information for further human handling and in which occupation it is used. AI may enhance or augment skills through, for example, the increased use of high-performance work practices, or it may increase work pace constra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 30 publications
(31 reference statements)
0
8
0
Order By: Relevance
“…Holm and Lorenz (2022) also demonstrate that AI's effects on workers depend on how the technology is used in a job (i.e., either by providing orders to human workers or by providing information for human worker decision making) and the skill level of workers. For high‐ and mid‐skilled workers, using AI daily to support decision making can enhance workers' skills by facilitating high‐performance work practices, such as teamwork and job rotation.…”
Section: Resultsmentioning
confidence: 99%
“…Holm and Lorenz (2022) also demonstrate that AI's effects on workers depend on how the technology is used in a job (i.e., either by providing orders to human workers or by providing information for human worker decision making) and the skill level of workers. For high‐ and mid‐skilled workers, using AI daily to support decision making can enhance workers' skills by facilitating high‐performance work practices, such as teamwork and job rotation.…”
Section: Resultsmentioning
confidence: 99%
“…Implementing a Healthcare 4.0 system requires the careful consideration of process improvement as part of the overall plan to achieve maximum benefits from technology adoption [ 117 ]. In the absence of a strategy that indicates a precise and coherent direction for the evolution of organizational and technological models, it is easy to get lost within an ever-increasing range of technologies, and perhaps end up choosing and introducing advanced digital solutions in an organizational context that is unable to grasp all the advantages to transform the competitive landscape and improve organizational performance [ 52 ].…”
Section: Resultsmentioning
confidence: 99%
“…In fact, software that uses BD efficiently can flag any inconsistencies between a patient’s medical history and their drug allergies with the medications they are taking, thus alerting the referring physician to discontinue therapy. BD can also identify chronically ill citizens, providing them with preventive actions to avoid clogging emergency channels, such as the emergency room [ 117 , 118 , 123 ].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the impact of AI varies according to the skill level of the job. For example, Holm and Lorenz (2022) found that using AI to support decision-making in high-skill jobs can lead to less autonomy but also a faster pace of work, less monotony, more learning, and greater use of a range of high-performance work practices. In middle-skilled jobs, the impact of using AI to make decisions is similar, albeit to a lesser extent, while using AI to give instructions leads to a faster pace of work, greater autonomy, and less learning.…”
Section: 2020)mentioning
confidence: 99%